Empowerment, job satisfaction and organizational commitment: a comparative analysis of nurses working in Malaysia and England - Nora Ahmad; Oranye, Nelson Ositadimma
Aims To examine the relationships between nurses empowerment, job satisfaction and organizational commitment in culturally and developmentally different societies. Background Employment and retention of sufficient and well-committed nursing staff are essential for providing safe and effective health care. In light of this, nursing leaders have been searching for ways to re-engineer the healthcare system particularly by providing an environment that is conducive to staff empowerment, job satisfaction and commitment. Methods This is a descriptive correlational survey of 556 registered nurses (RNs) in two teaching hospitals in England and Malaysia. Results Although the Malaysian nurses felt more empowered and committed to their organization, the English nurses were more satisfied with their job. Conclusion The differences between these two groups of nurses show that empowerment does not generate the same results in all countries, and reflects empirical evidence from most cross cultural studies on empowerment. Implications for nursing management Nursing management should always take into consideration cultural differences in empowerment, job satisfaction and commitment of nursing staff while formulating staff policies.